Association of serum hepcidin with prostate-specific antigen levels in men from high Andean cities of Peru - Alcantara-Zapata, Diana; Thiersch, Markus; Gonzales, Gustavo F. (International Journal of Health Sciences, 2023)
Objective: The prostate-specific antigen (PSA) is the primary biomarker to diagnose prostate cancer. Hepcidin has been reported as an alternative for this diagnosis; however, it is unclear how PSA and hepcidin function at high altitude (HA). This study aims to assess the association between hepcidin with PSA in HA residents chronically exposed to hypobaric hypoxia. Methods: We retrospectively examined data of 70 healthy males (aged 18–65-years-old) from four different altitudes cities in Peru: Lima (<150 m), Huancayo (2380 m), Puno (3800 m), and Cerro de Pasco (4320 m). Serum hepcidin, testosterone, and PSA were analyzed by chemiluminescence immunoassay. HA parameters (hemoglobin [Hb], pulse oxygen saturation [SpO2], and chronic mountain sickness [CMS] score) were also included in the study. Bivariate analyses and a multivariate linear mixed model were used to evaluate the association between hepcidin and PSA, adjusted by HA parameters, age, and body mass index (BMI). Results: Cases of excessive erythrocytosis (EE) (Hb >21 g/dL) were observed in the three highest cities. Hepcidin was positively correlated with Hb, CMS score, and BMI (P ≤ 0.05). Hepcidin was higher in Huancayo with respect to Puno, while PSA was lower in Cerro de Pasco in regard to Puno and Lima (P ≤ 0.05). Neither hepcidin nor PSA was increased by altitude in each city (P > 0.05). We did not find an association between hepcidin and PSA, even adjusted by age, BMI, Hb, and SpO2 (P ≤ 0.05). Conclusion: These findings showed no association between hepcidin and PSA levels in healthy residents at HA.